Glucagon-Like Peptide-1 and Blood Pressure in Young and Healthy Adults from the General Population. Issue 2 (February 2015) - Krisai, Philipp; Aeschbacher, Stefanie; Schoen, Tobias; Bossard, Matthias; van der Stouwe, Jan Gerrit; Dörig, Laura; Todd, John; Estis, Joel; Risch, Martin; Risch, Lorenz; Conen, David
<x xml:space="preserve">Abstract</x> Hypertension and diabetes mellitus are highly correlated, but the underlying mechanisms are only partly understood. Therefore, the aim of our study was to investigate the relationships between plasma levels of glucagon-like peptide-1, a key factor in the regulation of glucose homeostasis, and various blood pressure indices. Healthy adults aged 25 to 41 years were enrolled in a population-based study. Established cardiovascular disease, diabetes mellitus, or a body mass index >35 kg/m2 were exclusion criteria. Fasting plasma glucagon-like peptide-1 levels as determined with a novel high-sensitive assay and ambulatory blood pressure data were available in 1479 participants not using antihypertensive treatment. Median age of our population was 38 years. Mean systolic and diastolic blood pressure across increasing glucagon-like peptide-1 quartiles were 120.6, 122.8, 123.2, and 124.9 mm Hg and 77.1, 78.7, 78.9, and 79.9 mm Hg, respectively. We found a linear relationship of glucagon-like peptide-1 with 24-hour ambulatory blood pressure after multivariable adjustment (β per 1 log-unit increase 2.01; 95% confidence interval, 1.02–3.00; P<0.0001 for systolic and 1.22; 0.47–1.97; P=0.002 for diastolic blood pressure). In separate analyses, glucagon-like peptide-1 was significantly related to both awake (β per 1 log-unit increase 2.05; 1.02–3.09; P=0.0001 for systolic and 1.15; 0.35–1.96; P=0.005 for diastolic blood pressure) and asleep blood pressure (β per 1 log-unit increase 1.34; 0.26–2.42; P=0.01 for systolic and 1.05; 0.26–1.84; P=0.009 for diastolic blood pressure). In conclusion, plasma levels of glucagon-like peptide-1 are significantly associated with both systolic and diastolic blood pressure levels.